ISLAMIC RELIGIOUS EDUCATION IN THE DIGITAL AGE: THE TRANSFORMATION OF AI-BASED AND ADAPTIVE LMS LEARNING APPROACHES - Abdul Wahab Syakhrani (Indonesian Journal of Education (INJOE), 2026)
Rapid developments in digital technology have driven a fundamental transformation in Islamic Religious Education (IRE), demanding the adaptation of learning approaches relevant to the characteristics of Generation Z and the demands of the Society 5.0 era. This article aims to critically examine the transformation of PAI learning approaches through the integration of Artificial Intelligence (AI) and adaptive Learning Management Systems (LMS) as a response to the challenges of the digitalisation of Islamic education. This study employs a qualitative method using a literature review approach. The findings indicate that the integration of AI in PAI offers precise personalised learning through intelligent chatbots for discussions on fiqh and akhlak, an automated evaluation system based on deep learning for Qur’anic memorisation, and adaptive content generated by generative AI. Meanwhile, adaptive LMS facilitates responsive learning differentiation tailored to the diversity of students’ potential, creating a holistic educational ecosystem integrated between school and home, and enhancing learning engagement through gamification based on Islamic values. However, the implementation of these two technologies faces complex ethical and structural challenges, including the risk of AI hallucinations, the privacy of students’ spiritual data, the digital infrastructure gap between urban and rural areas, and the low digital competence of some PAI teachers. This article concludes that the success of digital transformation in Islamic Education requires a triple-helix synergy between artificial intelligence, the human wisdom of teachers, and an ethical framework based on maqashid al-shariah to ensure that technology functions as a wasilah (means) that strengthens the sacred mission of Islamic education, rather than as a ghayah (end) that reduces the essence of spirituality. Proposed policy implications include strengthening madrasah digital infrastructure, implementing continuous teacher training programmes, and developing a data governance framework based on the principles of hifz al-'ird and hifz al-'ilm.